Improving Students’ Grammar Competence through Discovery Learning for Islamic Education Program - Darussalam, Ahmad; Fahrinawati, Fahrinawati (The Art of Teaching English as a Foreign Language (TATEFL), 2023)
AbstractThis research aims to improve students’ grammar competence by using Discovery Learning for student of Islamic education program at STIT Ibnu Rusyd Tanah Grogot. Discovery learning is one of learning model of student-centered learning approach. The research method is classroom action research (CAR). This research applied two cycles. From the pre-test, the mean score got 60.45. The first cycle, the mean score got 70.5 and second cycle got 80.1. It showed the significant improvement from pre-test and post-test. This method is an endeavor that goes beyond merely addressing issues, simultaneously seeking scientific evidence to underpin problem-solving. This outcome demonstrated the positive impact of discovery learning on enhancing the grammar proficiency of students in the Islamic education program. Discovery learning enhances students' foundational knowledge of grammar, fosters their motivation to learn grammar, sparks their grammar curiosity, nurtures their grammar creativity, facilitates the acquisition of both factual information and an in-depth understanding of grammar analysis, and boosts students' self-confidence to use grammar perfectly. The authors recommend to search more and more about discovery learning for the learning and teaching English grammar. Further studies are still needed to complete the conclusions in this research. The development of teaching materials in adapting this teaching model is very necessary to add to the repertoire in developing grammar teaching materials.